2022
DOI: 10.1200/jco.2022.40.4_suppl.646
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in comprehensive genomic profiling in older patients with gastrointestinal malignancies.

Abstract: 646 Background: Limited data guides the management of older adults with cancer, a patient population that continues to be under-represented in clinical trials. Comprehensive Genomic Profiling (CGP) drives the enrollment on biomarker-based trials and may inform treatment selection. This analysis aims to evaluate the use of CGP in older patients with gastrointestinal (GI) malignancies and to compare results of genomic profiling across age groups. Methods: Clinical CGP results derived from Next Generation Sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…61 A recent analysis of comprehensive genomic profiling in older adults with gastrointestinal cancers found that 55.7% of patients who underwent molecular profiling were aged <65 years, and patients aged ≥75 years were underrepresented, despite the existence of an age-associated increase in high tumor mutational burden. 62 Ensuring that older patients of color receive the latest standard of care, including molecular profiling, may help to mitigate disparities in cancer treatment and survival outcomes.…”
Section: Biologic Features Of Tumorsmentioning
confidence: 99%
“…61 A recent analysis of comprehensive genomic profiling in older adults with gastrointestinal cancers found that 55.7% of patients who underwent molecular profiling were aged <65 years, and patients aged ≥75 years were underrepresented, despite the existence of an age-associated increase in high tumor mutational burden. 62 Ensuring that older patients of color receive the latest standard of care, including molecular profiling, may help to mitigate disparities in cancer treatment and survival outcomes.…”
Section: Biologic Features Of Tumorsmentioning
confidence: 99%